Research advances in the diagnosis and treatment of intradialytic hypotension during maintenance hemodialysis - Wang Jin-xin; Zhang Yi-xian; Lu Yue; Guo Si-ru; Miao Li-ning; Sun Jing (Linchuang shenzangbing zazhi)
Maintenance hemodialysis（MHD）is an important renal replacement therapy for patients with end-stage renal disease.However, when body fluid is removed too fast during dialysis as to exceed the rate of plasma supplement and the related cardiovascular, nervous, hormonal and other compensatory reactions, intradialytic hypotension（IDH）causes damage to multiple organs and systems and even endangers the lives of MHD patients.However, with a deepening mechanistic understanding of IDH,its occurrence of IDH has declined and the prognosis of MHD patients has been improved with the emergence of hypothermic dialysis, biofeedback system and intermittent infusion hemodiafiltration in recent years.Here both domestic and foreign IDH-related researches were summarized to provide references for further studies on the prevention and treatment of IDH.